Caste Hierarchy among Hill-Originated Caste Group: A Sociological Study of Kapan Area of Kathmandu Valley - Ghimire, Sumant; Adhikari , Shukra Raj (International Research Journal of MMC, 2026)
Caste is a major social stratification system in Nepali society. It is a part of social discourse. It has become a burning issue of contemporary Nepali society. In this context, this research aims to identify the caste-based hierarchy in the area of Kapan under the Kathmandu valley. The study followed descriptive and analytical research designs through the qualitative research approach. Qualitative data were adhered using case study and content analysis methods. Thus, primary data were collected from twenty-three case study narratives detailing individuals' experiences with caste based hierarchical relationship in their daily lives. The field study for data collection was carried out in July 2025.hose cases were selected using purposive and snowball sampling methods. Additionally, key informants’ interview method was applied to collect and cross check the information of cases. The content analysis method had been applied as the thematic form to analyze both primary and secondary data. The findings of the study show the continuation of caste hierarchy to shape social relations, albeit with a shift away from more overt forms of de facto exclusion and a greater emphasis on negotiation. Caste relations in Kapan reveal a pattern of ‘continuity within change’, while the ideology of purity and hierarchy remains culturally powerful, the everyday realities of enforcement have softened. This study contributes to a better understanding of how caste-based structures encounter, adapt, and evolve in urban settings.